Beyond four walls: The effects of non-Curricular Activities Involvement on the Academic Performance of the De La Salle University Bachelor of Science in Accountancy Students - Gallardo, Erin Maxine C. (Animo Repository, 2023)
Non-curricular activities (NCAs), including extra-curricular activities and co-curricular activities, continue to be imminent in modern times as avenues for Bachelor of Science in Accountancy (BSA) students to showcase their passion, interests, and skills outside their academic responsibilities. Aforesaid initiatives to promote holistic and developmental learning continue to be a serious topic of debate instigating the stigma that such activities consume the time that the students could have spent on their academic pursuits. Due to adversities and inadequacies of prior literature, NCA involvements impose reluctance as these are believed to be extra tedious and burdensome for the students. As such, this study aims to examine the effects of involvement in NCAs on the academic performance of the BSA students from different batches in Term 1, A.Y. 2022-2023 of De La Salle University. A sample of 292 students of the 1,068 total population of BSA students in the university were surveyed and analyzed using quantitative and qualitative measures. Upon a thorough investigation of the gathered statistical data’s Descriptive statistics, Proportional-Odds Cumulative Logistics Regression Model, and Qualitative Content Analysis, hypothesis testing affirmed that the significance of the effects of the NCA involvement in the academic performance of the students and the moderating effects of batch ID numbers were not evident suggesting no positive nor negative significant effects of NCA involvement in the academic performance of the BSA students. The study’s fruitful discussions of discourses and implications are of beneficial contributions to BSA students, parents, teachers, school organizations, Commission on Higher Education (CHED), and the academe.